BENDA CAGAR BUDAYA DAN SITUS: SEBUAH TINJAUAN YURIDIS - Dendi Eka Hartanto S. (Berkala Arkeologi, 1997)
A juridical fact that is quite alarming occurred after Law of the Republic of Indonesia Number 5 of 1992 concerning Cultural Conservation Objects was enacted on March 21, 1992. The juridical fact referred to is the fact that so far there has been a misconception, especially at the elite level of decision making in inemabami. nature of cultural heritage objects and sites. A concrete example is the Attachment to the Decree of the Director General of the Ministry of Education and Culture Number 0248 / Fl.IV / J.93 concerning Guidelines for Implementing Procedures for the Registration of Cultural Heritage Objects. Where in one of the forms is entitled Intangible Objects Inspection, but the content contained in it is about the site, with the editorial saying Site Serial Number and Site Name. Even though we know that theoretically and juridically, the essence of intangible cultural heritage objects is clearly not the same as the nature of a site.